EDUCATION OF ACCOUNTING PROFESSIONS AND STUDENT PERSEPTOIN TO INTEREST CAREER PUBLIC ACCOUNTING - Octaviani, Andri; Mulyadi, Mulyadi (STIE AUB Surakarta, 2018)
The purpose of this study is to find out: 1) To determine whether there is an influence of Accounting Profession Education to the career interests of public accountants students accounting skills program STIE AUB Surakarta. 2) To know whether there is influence of Student Perseption to career interest of public accountant student of accountancy program of STIE AUB Surakarta. This research is a descriptive quantitative research. The population of this research is the final year accounting student STIE AUB Surakarta. The sample of this research is 200 students taken by proportional sampling. Data collection techniques used were questionnaires and documentation. Data analysis technique is done by multiple linear regression. The results of this study are as follows: (1) Accounting Profession Education has a significant influence on the public accountant's interest in the amount of 0.000, 2) Student Perseption has a significant influence on entrepreneurship intentions towards entrepreneurial intentions of 0.003. Based on the calculation of the coefficient of determination can be said that 20.7% interest in careers public accountant STIE AUB Surakarta students can be influenced by the variables education accounting profession, student Perseption. Furthermore, the rest is 79.3% influenced by other factors, namely socio demographic factors, attitude factors, and contextual factors.Â Keywords: Accounting Profession Education Student Perception and Interest in Public Accountant Career